2017
DOI: 10.14241/asgp.2017.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermal history of the lower Carboniferous Culm Basin in the Nízký Jeseník Mts. (NE Bohemian Massif, Czech Republic and Poland)

Abstract: Raman microspectroscopy of organic matter, vitrinite reflectance and fluid inclusion data were used to reconstruct the thermal history in the lower Carboniferous accretionary prism of the Culm Basin in the Nízký Jeseník Mts. (NE Bohemian Massif). The model involves the Variscan (mid-late Carboniferous) burial diagenesis, which was overprinted by a post-Variscan, probably Permian and/or early Mesozoic, thermal pulse(s) in its central and western parts. The latter may have been related to advective heat transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
(231 reference statements)
0
3
0
Order By: Relevance
“…The rock samples were cut perpendicular to the bedding and from these rock pieces standard polished slides were prepared for vitrinite reflectance measurements (R' max -mean apparent maximum reflectance, R' min -mean apparent minimum reflectance and VR omean random vitrinite reflectance) and laser Raman spectroscopy. In the case of the highly disordered low-grade OM which occurs within the diagenetic zone such type of sample can be used efficiently (Rahl et al 2005;Kouketsu et al 2014;Wilkins et al 2014Wilkins et al , 2015Lünsdorf 2016;Botor et al 2017a;Henry et al 2019;Zhang and Li 2019). However, in highordered OM (particularly in graphite) several authors have shown that the polishing of a sample could cause a change in the Raman record (e.g., Katagiri et al 1988;Wopenka and Pasteris 1993).…”
Section: Samples and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rock samples were cut perpendicular to the bedding and from these rock pieces standard polished slides were prepared for vitrinite reflectance measurements (R' max -mean apparent maximum reflectance, R' min -mean apparent minimum reflectance and VR omean random vitrinite reflectance) and laser Raman spectroscopy. In the case of the highly disordered low-grade OM which occurs within the diagenetic zone such type of sample can be used efficiently (Rahl et al 2005;Kouketsu et al 2014;Wilkins et al 2014Wilkins et al , 2015Lünsdorf 2016;Botor et al 2017a;Henry et al 2019;Zhang and Li 2019). However, in highordered OM (particularly in graphite) several authors have shown that the polishing of a sample could cause a change in the Raman record (e.g., Katagiri et al 1988;Wopenka and Pasteris 1993).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…In the past few decades, the development of optics (including lasers) and computing has influenced progress in the Raman spectroscopy technique which allows for detailed study of OM and their thermal transformation (e.g., Beyssac et al 2002aBeyssac et al , b, 2003aJehlička et al 2003;Rahl et al 2005;Aoya et al 2010;Kouketsu et al 2014;Lünsdorf et al 2014;Lünsdorf 2016;Wilkins et al 2014Wilkins et al , 2015Botor et al 2017a;Henry et al 2018Henry et al , 2019Zhang and Li 2019). The Raman spectrum of OM is composed of firstorder (1000-1800 cm -1 ) and second-order (2500-3350 cm -1 ) regions (e.g., Pasteris and Wopenka 1991;Beyssac et al 2002a).…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation